Implementasi Tri Hita Karana Dalam Mengembangkan Sikap Sosial Religius Siswa Hindu Di SMPN 1 Balai Riam - Pawang, Pawang; Sumarni, Nyoman (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
Every human being needs a safe, peaceful and peaceful life. This will be possible if everyone is able to look after each other. Maintaining a harmonious relationship with God, maintaining a harmonious relationship with fellow humans and a harmonious relationship with the natural environment. In Hinduism, these three relationships are called Tri Hita Karana, namely the three causes of happiness. Understanding and implementing these three concepts needs to be done as early as possible, considering the negative impacts of technological developments that cannot be avoided. Students at SMPN 1 Balai Riam have a sufficient understanding of the Tri Hita Karana concept. You already have a good understanding of the concepts of parhyangan, pawongan and palemahan. The implementation of understanding the Tri Hita Karana concept to further develop students' social attitudes is carried out using several strategies, namely a) Carrying out prayers together and individually; b) carrying out social humanitarian activities through maintaining good relations with teachers, maintaining good relations with students, maintaining good relations between students and the community; c) Environmental Cleaning Activities carried out in accordance with the program established by the school